The Components of 'One World – One Health' Approach. (November 2013) - Calistri, P.; Iannetti, S.; L. Danzetta, M.; Narcisi, V.; Cito, F.; Di Sabatino, D.; Bruno, R.; Sauro, F.; Atzeni, M.; Carvelli, A.; Giovannini, A.
Summary: The interaction between living beings, including men, animals and pathogens, sharing the same environment, should be considered as a unique dynamic system, in which the health of each component is inextricably interconnected and dependent with the others. Nowadays, a new integrated One Health approach is reflecting this interdependence with a holistic view to the ecological system. The One Health approach can be defined as a collaborative and a multidisciplinary effort at local, national and global level to guarantee an optimal healthy status for humans, animals and environment. Strictly related to the One Health concept is to be considered the control of infectious diseases, which have influenced the course of human history. Four different components might be identified as key elements within the 'One World – One Health' (OWOH) approach: the geographical component, the ecological one, the human activities and the food‐agricultural ones.